Exploring English Learning in Indonesia: A Bibliometric Analysis from 2013 to 2022 - Jafar, Muhammad; Ammade, Salasiah; Ariani, Nina (FKIP Universitas Lampung, 2024)
Abstract: Exploring English Learning in Indonesia: A Bibliometric Analysis from 2013 to 2022. Research on English language learning in Indonesia has been widely done by many scholars from various aspects. Yet, research on documents about English learning in Indonesia within the last ten years in the form of bibliometrics analysis is still limited, and this research is going to fill the knowledge gap. The purpose of this study was to examine the state-of-the-art documents relevant to research in English learning in Indonesia using Scopus indexed articles. The data for this study were obtained from the Scopus database. The study uses VOS viewer to analyze keywords from 200 Scopus papers on learning English in Indonesia. Furthermore, the analysis of the Scopus database search results visualizes the characteristics and trends of journals, authors, and topics related to English learning research in Indonesia. Regarding the analysis result, publications on English learning in Indonesia have been published in 51 journals. Furthermore, Indonesian scholars were positioned as the authors lead with 183 documents publication on the English learning issue. Talking about institutional affiliation of authors who produce most research publication on English learning, Universitas Pendidikan Indonesia (19 publications) is the lead institutional followed by Universitas Negeri Makassar (19 publications). Concerning emerging themes in the research of English learning in Indonesia, the theme “Impact implementation teaching English” is the most frequent themes for the research. About the top issue cited, the most issued cited deals with English as an online communication, followed by strategies in language learning. This research contributes to the formation of more relevant research by becoming a reference for further researchers in identifying the position of contribution to the creation of more relevant research. Keywords: bibliometric analysis, English learning, scopus database, VOSviewer, Indonesia.DOI: http://dx.doi.org/10.23960/jpp.v14.i1.202428